Heritage and Tourism - In the age of digital transition and pandemic - Ronchi , Alfredo (Technical Annals, 2022)
Digital transition together with all the related side effects plus the pandemic imposed a true stress test to tourism and cultural institutions. Extended lockdowns deeply impacted citizens’ lifestyle, significantly reducing social life and cultural enjoyment. Following the fil-rouge of the evolution of tourism in different forms up to overtourism impacting both residents and heritage. The paper explores the key indicators of overtourism and related causes. From the advent of models based on the number of visitors and the carrying capacity of tourist locations, to the most recent assessments which also consider visitor behaviour, time dimensions and concentration phenomena of people in certain places. The term overtourism is an umbrella that covers a wide range of causes including urban planning, infrastructures, city managers, different stakeholders, citizens and of course tourists and daily visitors. This to do not forget undertourism and its origins.